Relationship between noise intensity and increased blood pressure in workers - Fitriyani, Darul; Buenita, Buenita; Bukit, Rosmeri br; Nainggolan, Efendi S (Buletin Kedokteran & Kesehatan Prima, 2024)
Occupational noise, particularly from industrial machinery and equipment, is a potential risk factor for elevated blood pressure. This cross-sectional study aimed to investigate the association between noise intensity and blood pressure changes among workers in the GCS department of PT. Pertamina EP Asset 1 Pangkalan Susu Field. All workers in five GCS units (n=30) participated. Noise intensity was measured using a sound level meter, and blood pressure was measured before and after work. Data analysis employed chi-square and paired t-tests with a significance level of 5%. Results showed no significant association between noise intensity and systolic blood pressure increase (p=0.317). However, a significant relationship was found between noise intensity and diastolic blood pressure increase (p=0.001). It can be concluded that there is a significant difference in systolic and diastolic blood pressure before and after work. Although noise intensity does not directly affect systolic blood pressure, it has a significant impact on increasing diastolic blood pressure.